Training of Forensic Experts: Pages of History - N. V. Mikhaleva (Теория и практика судебной экспертизы)
Constant relevance of the issues of forensic experts’ training is linked to the role assigned to a forensic expert in court proceedings. The article gives an overview of the previous legal acts regulating the process of training experts in forensic science institutions of the Ministry of Justice of Russia. It is shown that many of their best practices are still being used today. Some of them were transformed due to changes in legislation. The author also pays attention to the issues of training experts in universities. The conclusion is made on the need of training forensic experts using both proven and new forms of education.